Erwin Schrödinger: a compreensão do mundo infinitesimal através de uma realidade ondulatória - Schmidt, Douglas Guilherme (2008)
This historical research analyses the initial period of construction of wave mechanics, as propounded by the Austrian physicist Erwin Schrödinger (1887- 1961), emphasizing his work from December 1925 to February 1926. During these months Schrödinger created the basis of his quantum theory and wrote his two earlier papers on this subject. They were published in the Annalen der Physik. The present dissertation analyses those two papers, and some of their precedents and immediate consequences. Special attention is given to the influence of the theory of matter waves of the French physicist Louis de Broglie (1892-1987) upon the development of Schrödinger s theory, as well as other works and relevant circumstances that contributed to the creation of wave mechanics. The dissertation also discusses the interpretation given by Schrödinger to his own theory, comparing it to the approach of other physicists of that time